Paola Buzi, Coptic Manuscripts 7: The Manuscripts of the Staatsbibliothek zu Berlin, Preussischer Kulturbesitz, Part 4: Homiletic and Liturgical Manuscripts from the White Monastery: With two documents from Thebes and two Old-Nubian manuscripts - Lundhaug, Hugo (Aethiopica, 2017)
Review